Efficacy of natrium diclofenac gels application after odontectomy of lower third molar by assessment of swelling based on the level of alpha amylase and imunoglobulin-g: research - Harmas Y. Yusuf; Lucky Riawan; Sulfiana (DiscoverSys Inc., 2021)
Objective: The study was conducted on 60 patients determined with non-probability method using consecutive random sampling techniques according to the subject's order of arrival to the Outpatient of Oral and Maxillofacial Surgery Dental Hospital Padjajaran University for wisdom teeth odontectomy.Material and Methods: Samples were divided into two groups, the treatment group (which was given diclofenac sodium gel) and the control group (which was not given diclofenac sodium gel). Initial data collection of facial dimensions and assessment of salivary alpha amylase levels were performed prior to odontectomy. Retrieval of data was carried out at 2 hours, 3 days and 7 days after the procedure of odontectomy under local anesthesia.Result: No difference in swelling after odontectomy of the mandibular third molar after given the application of diclofenac sodium gel based with no given the application of diclofenac sodium gel based on imunoglobulin G levels in the impaction classification class Ia, Ib, Ic, IIa, IIb, IIc, with p value >0.05.Conclusion: there is a difference in swelling in the group given sodium diclofenac gel and not given sodium diclofenac gel based on alpha amylase levels in the classification.